Penerapan Strategi Pembelajaran Active Knowledge Sharing untuk Meningkatkan Hasil Belajar IPA pada Materi Struktur dan Fungsi Bagian Tumbuhan pada Siswa Kelas IV SD Negeri Kaporo Kabupaten Kepulauan Sula - Yetni Marlina; Harina Sangadji (Jurnal Ilmiah Wahana Pendidikan, 2022)
This study aims to determine the results of learning science material on the structure and function of plant parts through the application of active knowledge sharing learning strategies to fourth grade students of SD Negeri Keporo, Sula Islands Regency. This research is a type of classroom action research (CAR) which consists of two cycles with research procedures, namely, planning, implementation, observation and reflection. Data collection techniques for research data consisted of observation, tests and documentation. Based on the results of research conducted on student learning outcomes in the implementation of the action cycle I, the level of student mastery reached an average value of 7.928 students while the KKM was 70. The students who had experienced individual mastery in Cycle II reached 80.95%, it was said to be successful even though there were still students. whose value is less than the expected KKM.